The Effect of Academic Stress and Time Management on Academic Procrastination, with Cyberloafing as an Intervening Variable, among Students of SMKN 8 Jakarta - Ahmad Syarif; Annisa Lutfia; Rizka Zakiah (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study analyzes the effect of academic stress and time management on academic procrastination, mediated by cyberloafing, among SMKN 8 Jakarta students. Using a quantitative approach, a sample of 257 students was selected from a 715-students population (grades 10 and 11) via proportional random sampling and the Slovin formula. Data were analyzed using PLS-SEM via SmartPLS 4.0 software. Outer model tests confirmed convergent validity, discriminant validity (HTMT < 0,90), and reliability (composite reliability and cronbach’s alpha > 0,70). Inner model evaluation yielded an R-Square of 0,082 for cyberloafing and 0,445 for academic procrastination. Direct effect tests proved academic stress (β = 0,402; t-value = 8,259; p-value = 0,000) and cyberloafing (β = 0,331; t-value = 4,702; p-value = 0,000) positively affect academic procrastination, while time management affects it negatively (β = -0,294; t-value = 5,651; p-value = 0,000). Academic stress positively affects cyberloafing (β = 0,238; t-value = 3,802; p-value = 0,000), whereas time management affects it negatively (β = -0,166; t-value = 2,742; p-value = 0,006). Cyberloafing positively mediates the effect of academic stress (β = 0,079; t-value = 3,558; p-value = 0,000) and negatively mediates the effect of time management (β = -0,055; t-value = 2,104; p-value = 0,035) on academic procrastination. Ultimately, academic procrastination is driven by seeking enjoyable activities, academic stress primarily stems from family expectations, effective time management requires distraction-free environments, and cyberloafing mostly involves social media use during class.